A Realistic Examination, International Comparison, and Chinese Reflections on the Allocation of Public Service Resources for National Fitness - Yang, ZongQian; Deng, Liang; Huang, XiaoLing (Quality in Sport, 2025)
This paper examines the allocation of public service resources for national fitness in China, providing a realistic assessment, international comparisons, and Chinese reflections. It highlights the growing importance of national fitness as emphasized in the 20th National Congress of the Communist Party of China, alongside the 14th Five-Year Plan for Public Service Development. The paper identifies key challenges in China’s public resource allocation for national fitness, including high costs, low efficiency, and regional imbalances. Acknowledging the growing demand for fitness services, it explores the inefficiencies caused by a government-dominated allocation system and the lack of market mechanisms. The paper compares international practices from the UK, US, and Germany, which have successfully integrated market mechanisms, legal frameworks, and digital technologies to enhance resource allocation efficiency and equity in public service provision. It draws lessons from these countries’ experiences, particularly in optimizing competitive market approaches, involving social participation, and ensuring legal and procedural transparency. Based on these insights, the paper proposes several reforms for China: optimizing resource allocation models by introducing market mechanisms, improving regional balance in resource distribution, advancing digital empowerment for better management, and strengthening performance evaluation systems to enhance service quality and efficiency. By adopting these strategies, China can overcome existing barriers and create a more effective and equitable national fitness public service system, contributing to the realization of its sports powerhouse goal.